THE INCIDENCE OF NON ULCER DYSPEPSIA AND ITS RESPONSE TO TREATMENT - KHAN, JEHANGIR; JAVED, MUHAMMAD (Journal of Ayub Medical College Abbottabad, 2001)
Background: This study was undertaken to identify Non Ulcer Dyspepsia (NUD) in young patients presenting with peptic ulcer like symptoms. Their response to treatment was also determined. Methods: 100 patients between the ages of 20-40 of both sexes were included in the study. Investigations done were Chest X-ray Plain Abdominal X-ray. ECG, ESR, LFTs Amylase Abdominal Ultrasound and upper G1 endoscopy. All, patients then received 6-week therapy with Omeprazole and Helicobacter Pylori eradication with Clarithromycin and tinidazole. Results: NUD was by far the most common cause (59°/o) in both the sexes. Response to therapy was unsatisfactory. Conclusions: This relatively newly discovered clinical entity should be kept in mind while dealing with patients presenting with refractory dyspeptic symptoms